PENGARUH TERAPI SYUKUR DALAM MENINGKATKAN KUALITAS HIDUP PASIEN TERINFEKSI HIV - Rahayu, Esti Kusuma; Azzam, Rohman; Yunitri, Ninik; Rayasari, Fitrian; Astuti, Widia; Ulina, Barita; Maemun, Siti (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
Background: Quality of life remains an important concern for people living with HIV/AIDS (PLHIV). The challenges experienced have a major impact on their well-being, including psychological aspects. This study aims to evaluate the effectiveness of gratitude therapy on the quality of life of PLHIV. Methods: This study is a pre-experiment with a total of 30 subjects at RSPI Prof. Dr Sulianti Saroso. The sample selection method is purposive sampling with inclusion criteria of adult ODHIV (age >18 years) and actively visiting RSPI Prof. Dr. Sulianti Saroso to take antiretroviral (ARV) drugs every month, while the exclusion criteria are pregnant women. Subjects will undergo gratitude therapy for six weeks. Gratitude therapy was measured with gratitude inventory instrument and quality of life with WHOQOL-HIV BREF instrument. Significant changes in average quality of life scores before and after gratitude therapy with Wilcoxon test. Results: The majority of participants were male (70%) with a median (IQR) age of 39.6 (26-52) years. After subjects received gratitude therapy, there was a significant improvement in quality of life, with a mean difference of 4.00 (95% CI: 3.00-5.65; SE 0.693; p-value <0.001) and an effect size measured by biserial rank correlation of 1.00. Conclusion: The findings of this study indicate that gratitude therapy has a significant and positive impact on improving the quality of life of PLWHA. Gratitude is a necessity in fostering a positive outlook on life. Gratitude therapy can be a standardised form of service in hospitals. Future research with qualitative studies to determine the magnitude of its effect on the psychology of PLHIV.